Intragenic Transcriptional cis-Antagonism Across SLC6A3 - Zhao, Ying; Yu, Jinlong; Zhao, Juan; Chen, Xiaowu; Xiong, Nian; Wang, Tao; Qing, Hong; Lin, Zhicheng (Molecular neurobiology, 2019)
A promoter can be regulated by various cis-acting elements so that delineation of the regulatory modes among them may help understand developmental, environmental and genetic mechanisms in gene activity. Here we report that the human dopamine transporter gene SLC6A3 carries a 5' distal 5-kb super enhancer (5KSE) which upregulated the promoter by 5-fold. Interestingly, 5KSE is able to prevent 3' downstream variable number tandem repeats (3'VNTRs) from silencing the promoter. This new enhancer consists of a 5'VNTR and three repetitive sub-elements that are conserved in primates. Two of 5KSE's sub-elements, E-9.7 and E-8.7, upregulate the promoter, but only the later could continue doing so in the presence of 3'VNTRs. Finally, E-8.7 is activated by novel dopaminergic transcription factors including SRP54 and Nfe2l1. Together, these results reveal a multimodal regulatory mechanism in SLC6A3.
Keywords: dospělí; Promoter Regions, Genetic; Transcription Factors; Humans; Dopamine Plasma Membrane Transport Proteins; transkripční faktory; nádorové buněčné linie; zvířata; Models, Biological; Minisatellite Repeats; Transcription, Genetic; mužské pohlaví; biologické modely; Adult; zesilovače transkripce; promotorové oblasti (genetika); Enhancer Elements, Genetic; proteiny přenášející dopamin přes plazmatickou membránu; Animals; lidé; Mice, Inbred C57BL; minisatelitní repetice; Male; Cell Line, Tumor; genetická transkripce; Haplotypes; haplotypy; myši inbrední C57BL